DNA strand specificity in promoter recognition by RNA polymerase. - Park, C S (1980)
DNA strand and enzyme subunit specificities involved in the interaction between E. coli RNA polymerase and T7 DNA were studied by photo-crosslinking techniques. In non-specific enzyme-DNA complexes, subunits, sigma, beta, and beta' were crosslinked to both strands of the DNA. Under conditions leading to specific enzyme-promoter complexes, however, only sigma and beta subunits were crosslinked. The sigma subunit was crosslinked preferentially to the non-sense strand at promoter sites. No such strand specificity was observed for the beta subunit. These results provide insight into the molecular mechanism of promoter recognition and indicate that the interaction between RNA polymerase and DNA template is different at promoters and at non-specific sites.